Cardiovascular disease and prevention among people living with HIV in South Florida. Issue 28 (16th July 2021) - Pyarali, Fahim; Iordanov, Roumen; Ebner, Bertrand; Grant, Jelani; Vincent, Louis; Toirac, Alexander; Haque, Tahir; Zablah, Gerardo; Kapoor, Kunal; Powell, Alexis; Boulanger, Catherine; Hurwitz, Barry; et al.
Abstract : Abstract: Antiretroviral therapy (ART) has improved survival of patients living with HIV (PLWH); however, this has been accompanied by an increase in cardiovascular disease (CVD). Although preventative measures for CVD among the general population are well described, information is limited about CVD prevention among PLWH. The goal of this study was to characterize the prevalence of CVD in our population and to assess the use of primary and secondary prevention. We performed a retrospective review of PLWH receiving primary care at a large academic center in Miami, Florida. We characterized the prevalence of CVD, CVD risk, and the use of aspirin and statins for primary and secondary CVD prevention. A total of 985 charts were reviewed (45% women, 55% men). Average age was 52.2 years. Average CD4 count was 568 cells/microL. 92.9% were receiving ART, and 71% were virologically suppressed. The median 10-year ASCVD risk was 7.3%. The prevalence of CVD was 10.4% (N = 102). The odds of having CVD was lower in patients on ART (OR 0.47, 95% CI: 0.25–0.90, P = .02). The use of medications for primary and secondary prevention of CVD based on current guidelines was low: 15% and 37% for aspirin respectively, and 25% and 44% for statins. CVD risk and rates of CVD are high among PLWH and receiving ART could protect against CVD. However, the use of medications for primary and secondary prevention is low. Increased awareness of CVD risk-reduction strategies is needed among providers of PLWH to decrease the burden of CVD. Abstract : Supplemental Digital Content is available in the text